The cloud of Thecla and the construction of her character as a virgin (παρθένος), martyr (μάρτυς) and apostle (ἀπόστολος) - Narro, Ángel, 1985- (2019)
En los Hechos de Pablo y Tecla (APlTh) aparece una nube en algunas de las escenas más importante de la narración. Este motivo es utilizado para resaltar la protección ofrecida por Dios hacia la joven y evoca el idéntico motivo que aparece en Éxodo guiando y protegiendo a los israelitas. Gracias a este tipo de ecos, el autor de APlTh intenta establecer la conexión entre ambos textos en la mente de sus lectores y construir, al mismo tiempo, el personaje de Tecla, caracterizada como virgen, mártir o apóstol en diferentes momentos de la narración.
In the Acts of Paul and Thecla(APTh)a cloud appears in the most important scenes of the tale. This motif is used to highlight the protection offered by God on behalf of the young woman and echoes that cloud appearing in Exodusguiding and protecting the Israelites. Thanks to thesekindsof echoes, the author of the APThtries to establish a connection between both scenes in his readers’ mindsand builds, at the same time, the character of Thecla, portrayed as a virgin, a martyr oran apostle in different scenesof the narration.
Keywords: Cristianismo -- Historia -- S.I-VI; Personajes bíblicos